Interactive E-Module Model of Transformation Geometry Based on Case (Creative, Active, Systematic, Effective) as A Practical and Effective Media to Support Learning Autonomy and Competence. - Abidin, Z. S. E. W.; Walida, S. E. (Brazilian Journal of Implantology and Health Sciences, 2019)
This study aims to develop an interactive e-module of Transformation Geometry based on some principles, e.g. creative, active, systematic, and effective (CASE) as a teaching material to support learning autonomy and student’s competence. In this research and development study includes some steps, e.g. preliminary study, product design and development (model), and product testing and assessment. In the preliminary study, based on student’s needs analysis, it was shown that most students were more interested in Transformation Geometry session by using interactive emodule as the teaching materials as it may enable the students to learn independently and understand easily. Therefore, it is necessary to develop an interesting and easily-understood teaching material model in the form of an interactive e-module. In the designing step, the initial draft produced a model with a systematic: introduction (instructions for using e-modules, material descriptions, prerequisites, learning objectives), learning activities that include: a description of the material and examples of questions, problem training, summaries, competency tests, instructions for practice answers, feedback, and reference lists. In product development (model), CASE-based interactive e-module models covering Transformation Geometry topic was created. The results of the product review by experts indicate that the product (model) has fulfilled in terms of validity. The product testing results showed that the interactive e-module model Transformation Geometry developed in this study is as the teaching material model that supports learning independence and has met the criteria of a practical and effective model.